DIFFERENCES IN INTERLEUKIN-23 SERUM LEVELS TOWARDS THE SEVERITY OF ACNE VULGARIS IN WOMEN - Wafi Banadzir Resya; Novi Kusumaningrum; Santoso Jaeri; Astika Widy Utomo (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Acne vulgaris is a chronic inflammatory disease in the pilosebaceous gland of the skin which can cause depression and anxiety. IL-23 is a cytokine that is involved in autoimmune diseases, including acne vulgaris. IL-23 affects the differentiation process of Th17 which further produces IL-17, an important component in the pathogenesis of acne vulgaris. IL-17 plays a significant role in the grade of skin damage caused by the inflammation process.Objective: To find out differences in IL-23 serum levels and the grade of AV severity in women.Methods: An observational study with a cross-sectional design approach conducted from June until October 2020 in 15 women with AV aged 15-25 years old, not consuming anti-inflammatory drugs, antibiotics, retinoid group of drugs and free from other inflammatory diseases. Subjects were divided into three groups based on the AV severity grade: specifically mild (n=5), moderate (n=5) and severe (n=5). Subjects had venous blood taken for IL-23 serum content by the ELISA method. Data on IL-23 serum content in the three groups were tested using the One-Way ANOVA method to determine the differenceResults: Average age from the 3 groups was 21 (17-23 ) years old. The results showed that there is no significant difference in IL-23 rate from the 3 groups of AV severities (p=0,490).Conclusion: : There is no significant difference of IP-23 rate between the 3 groups of AV severites in women.